Association of proximity and density of parks and objectively measured physical activity in the United States: A systematic review. (August 2015) - Bancroft, Carolyn; Joshi, Spruha; Rundle, Andrew; Hutson, Malo; Chong, Catherine; Weiss, Christopher C.; Genkinger, Jeanine; Neckerman, Kathryn; Lovasi, Gina
Abstract: One strategy for increasing physical activity is to create and enhance access to park space. We assessed the literature on the relationship of parks and objectively measured physical activity in population-based studies in the United States (US) and identified limitations in current built environment and physical activity measurement and reporting. Five English-language scholarly databases were queried using standardized search terms. Abstracts were screened for the following inclusion criteria: 1) published between January 1990 and June 2013; 2) US-based with a sample size greater than 100 individuals; 3) included built environment measures related to parks or trails; and 4) included objectively measured physical activity as an outcome. Following initial screening for inclusion by two independent raters, articles were abstracted into a database. Of 10, 949 abstracts screened, 20 articles met the inclusion criteria. Five articles reported a significant positive association between parks and physical activity. Nine studies found no association, and six studies had mixed findings. Our review found that even among studies with objectively measured physical activity, the association between access to parks and physical activity varied between studies, possibly due to heterogeneity of exposure measurement. Self-reported (vs. independently-measured) neighborhood park environment characteristics and smaller (vs. larger) buffer sizes were more predictive of physical activity. We recommend strategies for further research, employing standardized reporting and innovative study designs to better understand the relationship of parks and physical activity. Highlights: We reviewed research on parks and objectively measured physical activity. Measurement and reporting of park density and proximity is not standardized. The association of parks and physical activity was inconsistent across studies. Standardized measurement and reporting are needed for future meta-analyses.